Lifestyle changes and risks of criminal victimization - Miethe, Terance D. (Journal of quantitative criminology, 1990)
Routine activity/lifestyle theories have been used to explain temporal changes in crime rates, the social ecology of crime, and individuals' risks of criminal victimization. Using a panel of 33,773 individuals and 19,005 households at two points in time, the current study extends previous research by examining whether changes in lifestyles are associated with changes in individuals' risks of personal and property victimization. Changes in lifestyles which signal greater target visibility or exposure to motivated offenders (greater daytime and nighttime activity outside the home) and reduced guardianship (decreases in the number of household members) are generally associated with increased risks of both types of victimization. Persons who maintained high levels of nighttime activity outside the household were also more likely to remain victims at both time periods. However, “active” lifestyle changes (increased precautionary actions) did not have their expected impact on reducing victimization risks, and several other changes over time also were inconsistent with expectations. The paper concludes with a discussion of the role of “passive” and “active” lifestyle changes on victimization risks and the implications of our findings for developing sociological theories of criminal victimization.